Membrane trafficking in breast cancer progression: protein kinase D comes into play - Gutiérrez-Galindo, Elena; Yilmaz, Zeynep Hazal; Hausser, Angelika (Frontiers in Cell and Developmental Biology, 2023)
Protein kinase D (PKD) is a serine/threonine kinase family that controls important cellular functions, most notably playing a key role in the secretory pathway at the trans-Golgi network. Aberrant expression of PKD isoforms has been found mainly in breast cancer, where it promotes various cellular processes such as growth, invasion, survival and stem cell maintenance. In this review, we discuss the isoform-specific functions of PKD in breast cancer progression, with a particular focus on how the PKD controlled cellular processes might be linked to deregulated membrane trafficking and secretion. We further highlight the challenges of a therapeutic approach targeting PKD to prevent breast cancer progression.